Colletotrichum siamense, a Mycovirus-Carrying Endophyte, as a Biological Control Strategy for Anthracnose in Guarana Plants - Casas,Luana Lopes (2021)
Abstract Guarana, the fruit of Paullinia cupana, is known for its stimulating and medicinal properties by the Amazonian indigenous population and communities. However, it presents serious phytopathological problems, such as anthracnose disease caused by Colletotrichum spp. The objective of this study was to verify if C. siamense, a mycovirus-carrying endophytic fungus, could protect guarana seedlings, by reducing or by eliminating characteristic disease symptoms. Other physiological changes in the plant caused by the presence of this endophyte were also evaluated. The cuttings of the Cereçaporanga cultivar were dipped in a biological control suspension and planted in a specific substrate. After four months in the greenhouse, the seedlings were sprayed with a suspension of phytopathogen conidia, and a portion of these seedlings received the fungicide indicated for the crop to be compared with the control seedlings. After 28 days, the number of lesions, morphophysiological and macro characteristics, and leaf micronutrients were evaluated. The seedlings treated with C. siamense showed a lower percentage of lesions and an increased aerial part and root system compared to the other treatments. There were no significant differences between treatments regarding the percentage of macronutrients and micronutrients.